The Impact of ESG Rating on Stock Price Volatility (Evidence from COVID-19 and Russia-Ukraine Conflict) - Nasiri Kheshtmasjedi, Maryam (My University, 2024)
The prevalent effects of a financial market crisis are instability and increased stock price fluctuations. COVID-19 and the conflict between Russia and Ukraine are two recent crises that have affected the global economy and consequently hit the stock market. During these turbulent periods, financial activists strive to discover ways to mitigate the unsteadiness in the market. One factor that aggravates stock price fluctuations in crisis is individual firms' lack of transparency in disclosure. Financial market activists react violently to minor market changes when companies do not disclose enough information, exacerbating volatility. ESG indicators, which serve as benchmarks to demonstrate companies' responsibility towards the environment and society, can potentially influence stock price volatility. A higher ESG score can indicate the transparency of an economic enterprise and its ability to provide more information. Consequently, such companies are perceived as healthy and less risky, potentially reducing price volatility. Moreover, companies that have invested more in ESG initiatives tend to gain more popularity and reputation. This increased goodwill can shield them from negative news, leading to more stability after a shock. This study aims to investigate the role of ESG in maintaining firms' stability in the financial market during periods of turmoil. It specifically examines the impact of ESG on stock price volatility during two recent crises: COVID-19 and the Russia-Ukraine conflict. The study includes a comprehensive analysis of 3,240 European firms during the COVID-19 crisis and 3,466 European companies during the Russia-Ukraine conflict. The research employs the OLS regression and Difference-In-Difference model to investigate the relationship between ESG and stock price volatility. The companies are categorized based on ESG scores and divided into ten equal groups for the Difference-In-Difference model. The study focuses on the groups with strong and weak ESG scores to understand the impact of ESG on these two groups before and after the crisis. The OLS regression results during both crisis periods reveal a statistically significant negative relationship between ESG and stock price volatility. The study's results indicate that companies with better ESG scores have lower stock price volatility in both crises. The Difference-In-Differ ence model results also show that stock price volatility is generally lower for the strong ESG score group than for the weak ESG score group before and after the shock. This study confirms that stock price volatility increased after the shock of COVID-19 and the conflict between Russia and Ukraine. However, companies with strong ESG scores show more resilience, and their price fluctuation increases less after the shock than companies with weak ESG scores.
Keywords: corporate responsibility; ethical investing; COVID-19; societal responsibility; volatility (societal properties); fi=Taloustiede|en=Economics|; Master's Degree Programme in Finance